Partisipasi Masyarakat dalam Kualitas Penyusunan Rencana Pembangunan Jangka Menengah (RPJM) Desa Panduman Tahun 2020-2025 - Wafa, Ali; Siswanto, Edhi; Angin, Ria; Adawiyah, Putri Robiatul (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study aims to determine the level of participation/involvement of the village community in the process of preparing the Panduman Village RPJM 2020-2025. Using a qualitative method, the data was collected by conducting interviews with informants and reviewing the Panduman Village RPJM document. The data was analyzed to see the level of community participation, including the quality of program proposals against the 4 dimensions of Panduman Village's problems and potentials. The results showed that; The Panduman Village community actively involved themselves in the process of preparing the Panduman RPJMDes for the 2020-2025 period. Village community aspirations always focus on physical infrastructure development. The village community has been able to evaluate the performance of the previous village government, including identifying 4 dimensions of village problems and potentials. However, the alternative solutions proposed by the community are still unable to answer the problems and manage the village's potential in a sustainable manner.